2006
DOI: 10.1002/hep.21310
|View full text |Cite
|
Sign up to set email alerts
|

Lack of UCP2 reduces fas-mediated liver injury in ob/ob mice and reveals importance of cell-specific UCP2 expression

Abstract: Fatty liver is vulnerable to conditions that challenge hepatocellular energy homeostasis. Lipidladen hepatocytes highly express uncoupling protein-2 (UCP2), a mitochondrial carrier that competes with adenosine triphosphate (ATP) synthesis by mediating proton leak. However, evidence for a link between UCP2 expression and susceptibility of liver to acute injury is lacking. We asked whether absence of UCP2 protects ob/ob mice from Fas-mediated acute liver damage. UCP2-deficient ob/ob mice (ob/ob:ucp2 ؊/؊ ) and UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…On the contrary, there lacks sufficient information on whether replacement with UCP2 could alleviate NAFLD [30]. In fatty liver tissues, the lipid-laden hepatocytes express high levels of UCP2, whereas the expression of UCP2 in Kupffer cells decreases [40]. The present study demonstrates that UCP2 expression is significantly reduced in NPCs, but not PCs fractions of AKO livers.…”
Section: Discussionmentioning
confidence: 50%
“…On the contrary, there lacks sufficient information on whether replacement with UCP2 could alleviate NAFLD [30]. In fatty liver tissues, the lipid-laden hepatocytes express high levels of UCP2, whereas the expression of UCP2 in Kupffer cells decreases [40]. The present study demonstrates that UCP2 expression is significantly reduced in NPCs, but not PCs fractions of AKO livers.…”
Section: Discussionmentioning
confidence: 50%
“…TCDD elicited temporal and dose-dependent differential expression of UCP2 and UCP5. UCP2 is highly expressed in Kupffer cells, but not in healthy hepatocytes (Fulop et al, 2006). However, UCP2 is highly expressed in fatty liver hepatocytes (Fulop et al, 2006; Grav et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…UCP2 is highly expressed in Kupffer cells, but not in healthy hepatocytes (Fulop et al, 2006). However, UCP2 is highly expressed in fatty liver hepatocytes (Fulop et al, 2006; Grav et al, 2003). TCDD (30 μg/kg) induces fatty accumulation in C57BL/6 mouse liver (Boverhof et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies showed that, under conditions associated with increased hepatic UCP2 expression (e.g., fatty liver and endotoxin-mediated liver injury), cellspecific expression would change with UCP2 being expressed primarily in hepatocytes. UCP2 mRNA and protein levels were increased in hepatocytes from ob/ob mice (8,10). Bacterial lipopolysaccharide-injected rats showed increased expression of UCP2 mRNA in hepatocytes, whereas UCP2 mRNA levels were decreased in macrophages (9).…”
mentioning
confidence: 92%